Involvement of NFκB in the Production of Chemokines by Rat and Human Conjunctival Cells Cultured Under Allergenic Conditions. (August 2013) - Sakai, Osamu; Tamada, Yoshiyuki; Shearer, Thomas R.; Azuma, Mitsuyoshi
Abstract Purpose: The purpose of present studies was to determine the involvement of NFκB and STAT6 transcription factors in the production of cytokines by the fibroblasts and epithelial cells in conjunctiva. Methods: An in vitro model of allergic conjunctivitis was developed by sensitizing and challenging rat mast cells with anti-dinitrophenyl (DNP) IgE and DNP-BSA, and then using the conditioned medium to stimulate rat conjunctival fibroblasts. Chemokines (eotaxin-1, IL-8, and RANTES -- Regulated and Normal T cell Expressed and Secreted) released from cells into the medium was determined by ELISA. Human conjunctival fibroblasts and epithelial cells were also directly stimulated with exogenous cytokines tumor necrosis factor (TNF)-α or IL-4. Degradation of IκB-α and phosphorylation of STAT6 were assessed by immunoblotting. For inhibition of NFκB or STAT6 activation, upstream regulators IκB kinase and Janus protein tyrosine kinases (JAK) were inhibited by use of BMS-345541 and JAK inhibitor 1. An in vivo model of conjunctivitis was also produced in rats by intraperitoneal injection of ovalbumin (OA) with aluminum hydroxide and challenge at 21 d with OA eye drops. Results: Stimulated rat mast cells released TNF-α and IL-4. TNF-α induced NFκB activation in rat and human conjunctival fibroblasts and epithelial cells, and caused production and release of cytokines IL-8 and RANTES. IL-4 activation of STAT6 did not cause release of these cytokines. Only fibroblasts produced the eosinophil-recruiting cytokine, eotaxin-1, after treatment with TNF-α- plus IL-4. As observed in the cultured cells, allergic stimulation in the in vivo model caused degradation of IκB-α in conjunctiva, and infiltration of eosinophils and other inflammatory cells. Conclusion: Activated NFκB was found to be a major transcription factor for the release of cytokines from conjunctival cells and intensification of the allergic response. Inhibition of the NFκB pathway by therapeutic drugs may be an important objective for the treatment of human allergic conjunctivitis.